Religious Penetration in the Global Era: Case Study of Freedom to Choose Religion in the Family - Husna Ni’matul Ulya; Novi Fitia Maliha; Wening Purbatin Palupi Soenjoto (Jurnal Antologi Hukum, 2025)
Advances in technology and religious learning can be done through virtual media, but negative impacts can arise because religious figures are virtual. Technological advances in all aspects mark Indonesia's freedom of religion in this global era. And the reduced role model of religion at home and in the environment. There are many families consisting of more than one religion. The impact is that this is considered a natural thing in society. Based on the above assumptions, the researcher is interested in researching Religious Penetration in the Global Era (Case Study of Freedom to Choose Religion in the Family). This study uses qualitative research methods and case studies based on search, library, interview, observation, and triangulation techniques in finding and decomposing the data presented with the results of observations to be analysed descriptively. The study results show that religious freedom in the family should be based on positive reinforcement and constructive negative reinforcement to obtain behaviour that is by the correct legal and legal basis in applying religious freedom.